Effect Of Magnesium Oxide (Mgo) As An Antifungal Agent On Singgora Roof Tile. - Wan Hazwani Binti Wan Mohd Fakri (2022)
Singgora roof tile is a traditional heritage roof design widely use in Malay houses. Singgora made from moulded clay and burnt in kiln at high temperature. Basically, the characteristic of clay can absorb moisture that can thrive growth of fungi. Therefore, addition of magnesium oxide (MgO) as an antifungal agent can inhibit the growth of fungi on the tile. This research is conducted to investigate the effectiveness of MgO against the growth of fungi and to study additive of MgO on mechanical and physical properties in clay sample. Six different weight percentage (0, 5, 10, 15, 20 and 30 wt.%) of MgO been used as a parameter to find the optimum weight percentage that can be used in a clay production. The fungi from the genus Stachybotrys were streaked from Singgora tile and cultured for several days on potato dextrose agar (PDA). The colonies obtained were analysed using zone of inhibition (ZOI) using different weight percentage of MgO to test the effectiveness of antifungal by the presence of clear zone. Observation of ZOI for anti fungal 10 wt.% of MgO can reached up to 60 mm of diameter of clear zone. The clay samples at different composition of MgO were casted inside Plaster of Paris (POP) mould and burnt the samples at 800°C for 12 hours. In density and porosity test shows increased the composition of MgO can cause decreased the density value and increase the porosity percentage. Sample 30 wt.% had the highest porosity at 48% and low density at 2 g/cm3. Then, microstructure of clay samples was analysed under Scanning Electron Microscopy (SEM) to observed the pore and crack formation of the sample. Sample 20 wt.% and 30 wt.% had the highest crack formation of microstructure. Besides, Energy Dispersive Spectroscopy (EDS) was also used to detect the elements included silicon, oxygen, iron, lithium, aluminium, manganese and magnesium. Then, three bending point test was used to analysed the strength showed 0 wt.% was the highest strength at 9.394 MPa and begins to decreased when MgO was added. However, after added the MgO, 10 wt.% at 1.372 MPa had the higher strength among the MgO additive. Therefore, 10 wt.% of MgO was the optimum composition as an additive in clay production that high inhibit growth of fungi, low porosity and crack formation and have higher strength among the other addition of MgO in sample. eywords: Singgora, clay, magnesium oxide, antifungal, zone of inhibition.